2012
DOI: 10.1007/s00586-012-2486-6
|View full text |Cite
|
Sign up to set email alerts
|

Is hybrid surgery of the cervical spine a good balance between fusion and arthroplasty? Pilot results from a single surgeon series

Abstract: HS is comparable to ACDF and ADR in terms of safety and feasibility. Findings of shorter in-hospital stay and earlier return to work in HS group may be further explored in large, randomised controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
2
45
0
2
Order By: Relevance
“…36,39,40 Similar results between single-level and multilevel arthroplasty groups have been found in terms of reoperation rates and serious adverse events. 3 The existing literature compares either ACDF with HS or ADR with HS. 25,35,42 By combining ACDF and ADR in HS, the main objective is to restore or maintain motion where appropriate, or to favor bony fusion when indicated by the extent of the degenerative changes and hypermobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,39,40 Similar results between single-level and multilevel arthroplasty groups have been found in terms of reoperation rates and serious adverse events. 3 The existing literature compares either ACDF with HS or ADR with HS. 25,35,42 By combining ACDF and ADR in HS, the main objective is to restore or maintain motion where appropriate, or to favor bony fusion when indicated by the extent of the degenerative changes and hypermobility.…”
Section: Discussionmentioning
confidence: 99%
“…41 Moreover, several studies have shown that the duration of operation for ADR is much greater than for ACDF. 3,4,37,38 Although some long-term follow-up (at least 4 y) studies exist that suggest C-ADR is a safe option, [33][34][35] only a few article have considered the outcomes of HS, and these have had a maximum follow-up of 2 years. 6,10 Theoretically, HS should be intermediate between both ACDF and ADR in terms of intraoperative and postoperative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because not all diseased levels may meet acceptable criteria for CDA, some authors turned to hybrid surgery as an alternative to multilevel ACDF or CDA. Hey et al 12 conducted a prospective study with a minimum 2-year follow-up and found that hybrid surgery incorporating ACDF and CDA is comparable to ACDF and CDA in terms of safety and feasibility. Cardoso et al 4 evaluated a cervical hybrid arthroplasty (ACDF + Prestige ST cervical disc [Medtronic Sofamor Danek]) in patients with multilevel cervical spondylosis, and found that this hybrid cervical arthroplasty is a safe and effective alternative to multilevel fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The present biomechanical study shows that HS could maintain segmental motion of the operative levels and have less adverse influence on adjacent levels. Therefore, HS may be a safe and effective alternative for multilevel cervical degenerative disc diseases [9].…”
Section: Z Liao Et Al / Coupled Motion Of Cervical Spine In Three Lmentioning
confidence: 99%